INNOVATIONS AND INFORMATIZATION IN THE MODERN EDUCATION SYSTEM - Gaffаrov Yarash Khollievich (Bright Mind Publishing, 2026)
This article presents information on informatization, technologization, and innovation in educational processes. The rapid development of science and technology has created the foundation for the informatization of all spheres of public life. A country's place in the economy, human life, and the global community depends on the state of information technology development. The state of development of modern technologies depends primarily on the intellectual potential of society, including the development of the educational sphere.
Keywords: Technological process, integration, innovation, global, portable, modeling, strategy, communication, multimedia, information technology.